Kikuchi Fujimoto disease: a rare case report - Sourabh, Sumit; Jindal, Akriti; Singh, Ashiana (International Journal of Advances in Medicine, 2022)
Kikuchi disease, also known as Kikuchi histiocytic necrotizing lymphadenitis, was initially described in young Japanese women. It is a rare benign self-limiting disease of unknown cause usually characterized by fever and cervical lunphadenitis. It is diagnosed by doing excisional biopsy of affected lymph node. A case of young 20 years old female presented with complaint of fever and weight loss for 20 days along with cervical and axillary lymphadenopathy. Complete physical examination, radiological investigations and biochemical tests were done to rule out systemic lupus erythematous, non-Hodgkin lymphoma and tuberculosis. Only symptomatic treatment was done along with corticosteroids. Its diagnosis is important as it can be easily mistaken for other form of lymphadenitis. Clinician and pathologists’ awareness of this disorder is very necessary.